Overall Buckling Behavior and Design of Steel Stiffened Box Section Columns Under Axial Compression - Bing Shangguan; Jie Li; Qiu Zhao; Peng Chen; Furong Ruan; Huiteng Pei (Buildings)
This study experimentally and numerically investigated the overall buckling behavior of steel box column components. Two box section specimens were fabricated for axial compression tests. Prior to the tests, the material properties, initial geometric imperfections and residual stress were measured. In addition, an extended parameter analysis was conducted using a finite element model validated by experimental results to evaluate the impact of geometric defects and residual stresses on the bearing capacity of unstiffened and stiffened box section columns. A novel column curve was proposed based on massive datasets of parametric models. The short and long column specimens exhibited typical strength failure and buckling failure modes, respectively. The initial geometric imperfections and residual stresses slightly reduced the buckling strength from the models, with a maximum reduction in buckling strength owing to initial geometric imperfections of 5.2% and that owing to residual stresses of 6.52%. The unstiffened and stiffened box columns have the same stability coefficient when the slenderness ratio is the same. Additionally, the ultimate load capacity calculation formula for stiffened box columns proposed in this paper averages 2.20% higher than Class C curves in JTG D64-2015, lies between Japanese and U.S. codes, and demonstrates good accuracy.